2007
DOI: 10.1177/000313480707301210
|View full text |Cite
|
Sign up to set email alerts
|

Bullet Embolus to the Heart after Gunshot Wound to the Neck: A Case Report

Abstract: A 43-year-old woman presented with gunshot wounds to the neck, chest, and left thigh. Computed tomography of the neck and chest with intravenous contrast revealed a left common carotid pseudoaneurysm and a foreign body in the right atrium. Preoperative chest x-ray and CT scan confirmed a metallic foreign body in the right heart. At median sternotomy, the intracardiac foreign body could not be located using fluoroscopy. The foreign body (bullet) was subsequently removed in the cardiac catheterization laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The period and path taken varies widely. Previous studies have shown embolization to the heart’s right atrium and ventricle [ 12 ], pulmonary artery [ 13 ], and through the left brachiocephalic vein to the right ventricle [ 14 ]. There may also be aspiration of the bullet into the larynx following initial impact on the mandible [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The period and path taken varies widely. Previous studies have shown embolization to the heart’s right atrium and ventricle [ 12 ], pulmonary artery [ 13 ], and through the left brachiocephalic vein to the right ventricle [ 14 ]. There may also be aspiration of the bullet into the larynx following initial impact on the mandible [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Es habitual que se acompañen de manifestaciones como derrame pericárdico (1) o neumotórax como consecuencia de su trayectoria. Es mucho más infrecuente que estos cuerpos extraños lleguen a las cavidades cardíacas por impacto de proyectiles en otra localización anatómica como cuello (3)(4) o extremidades inferiores (5) , afectando estructuras vasculares y embolizando hasta el endocardio. En estos casos pueden no existir manifestaciones extracardíacas e incluso pueden encontrarse como hallazgo casual de un evento previo no estudiado en su momento.…”
Section: Discussionunclassified
“…Intravascular embolization of shotgun pellets or single bullets has been previously described to the brain, with or without catastrophic sequelae [ 3 8 ]. Whilst retrograde intravascular embolisation of intravascular missiles is a relatively infrequently described event [ 9 12 ], the radiologist and emergency department physician involved in assessment of firearm injury must be aware of the increased probability of both antegrade and retrograde intravascular embolisation in shotgun trauma. Missile embolization may not be suspected at the time of injury [ 13 ] or may be delayed [ 14 ].…”
Section: Discussion Of Findingsmentioning
confidence: 99%